Chromatic, Phenolic and Antioxidant Properties of Sorghum bicolor Genotypes - López Contreras, José Juan; Zavala García, Francisco; Urías Orona, Vania; Martínez Ávila, Guillermo Cristian Guadalupe; Rojas, Romeo; Niño Medina, Guillermo (Academic Press, 2015)
Chromatic, phenolic and antioxidant properties were evaluated in ten sorghum genotypes grown in Nuevo León, México. Lightness, Chroma and hue angle ranged from 64 to 83, 12 to 20 and 61 to 82 respectively, indicating that colour of the samples were located in the gray orange-yellow zone of the hue circle. Based on these results, samples were classified in three colour groups being Very Soft Orange, Slightly Desaturated Orange and Grayish Orange. Results in phenolics ranged from 796 to 15,949, 175 to 12,674 and 193 to 25,780 µgCE g-1 in total phenolics by Folin-Ciocalteu, total flavonoids by Aluminum Chloride and condensed tannins by Vanillin-HCl respectively. On the other hand, antioxidant capacity ranged from 1.20 to 93.83, 30.25 to 156.08 and 2.62 to 98.50 μmolTE g-1 in 2,2-diphenyl-1-picrylhydrazyl, 3-ethyl-benzothiazoline-6-sulfonic acid and Ferric Reducing Antioxidant Power respectively. Significant differences (p≤0.05) were observed in statistical analysis for both individual and group colour samples in chromatic, phenolics and antioxidant activity evaluations, showing ‘Rox Orange’ genotype and Grayish Orange colour group the highest levels.